2017
DOI: 10.21608/msnj.2017.187715
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Assertive Behaviour among Head nurses

Abstract: Assertiveness is the expression of one's feelings, beliefs, opinions, needs in a direct, honest and appropriate manner. Assertive not describe individual only also describe behavior, so that assertive behavior is a behavior which directly expresses individual's true, basic feelings, needs, desires, opinions and personal rights in a positive, productive way without denying the rights of others . The aim of the study: Identifying the factors affecting assertive behaviour among head nurses at Minia University Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Nurses are ethically obligated to question incorrect orders and advocate for patient rights [8,9]. Nurses, being the largest workforce in hospitals, are uniquely positioned to advocate for patient care changes, thereby strengthening inter-professional relationships and preventing workplace violence [10]. Studies have shown varying levels of assertiveness among nurses, with a significant proportion exhibiting limited assertiveness [11,12].…”
Section: Introduction a Background Of The Studymentioning
confidence: 99%
“…Nurses are ethically obligated to question incorrect orders and advocate for patient rights [8,9]. Nurses, being the largest workforce in hospitals, are uniquely positioned to advocate for patient care changes, thereby strengthening inter-professional relationships and preventing workplace violence [10]. Studies have shown varying levels of assertiveness among nurses, with a significant proportion exhibiting limited assertiveness [11,12].…”
Section: Introduction a Background Of The Studymentioning
confidence: 99%